Nudges as a suitable and effective intervention to improve hand hygiene compliance among healthcare workers in patient care settings: a narrative review - Wahab, Muhammad Taufeeq (International Journal of Infection Control, 2023)
Hand hygiene among healthcare workers (HCWs) is critical to preventing harm to patients in the process of healthcare delivery by minimising healthcare-associated infections (HCAI) in patient care settings. However, low compliance rates of hand hygiene plague healthcare, making it a global priority. Nudges are potentially a suitable and effective intervention to improve compliance among HCWs. In this review, nudges are defined as a method of intervention that attempts to influence people’s judgement, choice or behaviour in a predictable way, without forbidding any options or significantly changing economic incentives. This review aims to determine whether nudges are a suitable and effective intervention for improving hand hygiene compliance among HCWs in patient care settings. This review finds nudges suitable for inculcating professional handwashing habits as they are a form of ritualistic and automatic behaviour driven by unconscious processes, which can be influenced by social influences and environmental cues. A literature search conducted up until January 2022 identified 19 primary studies – 10 of which belonged to a systematic review – investigating the isolated effect of nudge interventions on improving HCW hand hygiene compliance in patient care settings. There is some indication that performance feedback may be effective, but significant heterogeneity of interventions and study designs make it difficult to conclude any further. Future research should employ study designs with minimal bias, use automated hand hygiene auditing systems and should address structural and resource-related constraints before evaluating nudge interventions.